Effect of stocking density on growth performance of African catfish Clarias gariepinus and water spinach Ipomoea aquatica in aquaponics systems with the addition of AB mix nutrient - Wiyoto, Wiyoto; Siskandar, Ridwan; Dewi, Ratih Kemala; Lesmanawati, Wida; Mulya, Muhammad Arif; Ekasari, Julie (Jurnal Akuakultur Indonesia, 2023)
Aquaponics is the cultivation of fish and plants in a series of systems, either in one container or in separate containers, by paying attention to the balance between fish, plants, and aquatic microorganisms. One of the obstacles in aquaponic activities is that vegetable growth is not optimal due to a lack of dissolved nutrients, so further research is needed to make better plant growth. This study aimed to evaluate catfish and water spinach growth performance in an aquaponic system by adding AB mix nutrients at different fish stocking densities. This study used a completely randomized design with three differences in stocking densities of catfish (150 fish/m3, 200 fish/m3, and 250 fish/m3) as test animals with four replications where AB mix was added to each treatment. The growth performance of catfish is better in control with a stocking density of 250 fish/m3 and without adding nutrients. The growth performance of catfish decreased with the addition of AB mix nutrients, while the growth of water spinach was better. The growth rate of catfish without adding AB mix nutrients was higher than in other treatments. In contrast, all treatments with the addition of AB mix increased the growth performance of water spinach, with the stocking density of catfish not affecting the growth of water spinach plants. Keywords: aquaponics, water spinach, catfish, growth ABSTRAK Akuaponik merupakan budidaya ikan dan tanaman dalam satu rangkaian sistem, baik dalam satu wadah maupun dalam wadah terpisah dengan memperhatikan keseimbangan antara ikan, tanaman dan mikroorganisme perairan. Salah satu kendala sistem akuaponik adalah pertumbuhan sayuran yang tidak optimal karena kurangnya nutrisi terlarut. Tujuan dari penelitian ini untuk mengevaluasi performa pertumbuhan lele dan kangkung dalam sistem akuaponik dengan penambahan nutrisi AB mix dan pada padat tebar ikan yang berbeda. Penelitian menggunakan rancangan acak lengkap dengan tiga perbedaan padat tebar ikan lele (150 ekor/m3, 200 ekor/m3, dan 250 ekor/m3) sebagai hewan uji sebanyak empat ulangan di mana nutrien AB mix ditambahkan disetiap perlakuan. Kinerja pertumbuhan ikan lele lebih baik pada perlakuan kontrol dengan padat tebar 250 ekor/m3 dan tanpa penambahan nutrisi AB mix. Performa pertumbuhan ikan lele menurun dengan adanya penambahan nutrisi AB mix, sedangkan pertumbuhan tanaman kangkung lebih baik. Laju pertumbuhan ikan lele dengan tanpa penambahan nutrisi AB mix lebih tinggi dibandingkan perlakuan lainnya, sedangkan semua perlakuan dengan penambahan AB mix meningkatkan performa pertumbuhan tanaman kangkung dengan jumlah padat tebar ikan lele tidak berpengaruh pada pertumbuhan tanaman kangkung. Kata kunci: akuaponik, kangkung, lele, pertumbuhan